Fault diagnosis of sensor pulse signals based on improved energy fluctuation index and VMD - Liu, Yuhu; Chen, Xiaolong; Mao, Yongfang; Chai, Yi; Jiang, Yutao (Frontiers in Physics, 2023)
Variational Mode Decomposition (VMD) has been widely applied in Sensor. However, the mode number and balance parameter limits VMD application seriously. To solve this problem, a novel method, which combines an improved energy fluctuation index (IEFI) and modified VMD (MVMD), is proposed in this study. In the proposed method, IEFI, provides better performance to resist the interference from random impulse by considering the periodicity of fault feature component. Consequently, it is applied to determine the initial center frequency for MVMD, which fixed problem of the mode number. Moreover, a novel balance parameter search strategy which can determine the optimal balance parameter adaptively are combined with MVMD whose stop condition is replaced by kurtosis to extract the fault feature. Simulation results indicate that the proposed method does well in detecting feature of periodic impulse signal from the signal that is polluted by some interference impulses. Moreover, the bearing fault diagnosis results demonstrate that the proposed method can detect bearing fault feature accurately. Furthermore, the method was validated with bearing fault data, and the results showed that the method can accurately extract the fault characteristics of the impulse signal and achieve fault diagnosis.